(untitled) (The Research of Medical Science Review, 2025)
BACKGROUND: Attention deficit hyperactivity disorder is a disorder that is marked by In-attention, hyperactivity and impulsivity that interferes with daily life, functioning and development. In our study, effects of cognitive behavioral therapy and motor learning techniques on adults with ADHD were studied and compared. OBJECTIVES: To apply different motor learning techniques and cognitive Behavioural therapy in order to determine whether combine effect of both or cbt alone were more effecting on adults with adhd. METHODOLOGY: In this randomized controlled trial, 30 participants were assessed by validated questionnaire; adult Self-Report Scale-V1.1 (ASRS-V1.1) for screening of ADHD. Random assignment was done by lottery method. The control group was given Cognitive Behavioural Therapy while the intervention group was given CBT and Motor Learning Techniques for 15 alternative days. The pre and post treatment scores were collected. RESULTS: In that study, 34 adults participated. Mean age of the CBT+Motor participants was 22.3529±1.16946 years and CBT was 22.1875±1.04682 with range from 18 to 40. All the participants have attention deficit hyperactivity disorder. Mean of CBT+Motor group was 21.65 and mean of CBT group was 24.94. There was no statistically significance between both groups (p-value 0.182). There was statistical difference in Montreal cognitive assessment score among both groups (p-value0.002) CONCLUSIONS: The frequency of attention deficit hyperactivity disorder was common among the adult population. Reduction in symptoms was seen in group given CBT+Motor learning techniques as compare to the group given CBT only.